Amendments of Russian constitution concerning international law and the BRICS - Kudryashova, Ekaterina; Verlaine, Michel; Shashkova, Anna (Revista de Investigações Constitucionais, 2020)
The paper presents the current constitutional reform in Russia focusing on the constitutional amendment concerning the international case law. The amended article 79 of the Constitution of Russian Federation restricts the international case law applicability in Russia. There was no polemic around the draft of the constitutional amendment and this restriction was accepted by experts, politicians and public without any discussion. To certain extent this unanimous acceptance could be explained by general positivistic trend in Russia. The amendment is in line with the positivistic approach to the international law formed in Russia recently. The strategic documents on the cooperation within BRICS are scrutinized showing that the positivistic approach is in line with the strategies of Russia announced previously. Based on the general scientific methods and on the method of academic foresight the authors made the following conclusions. The constitutional reform regarding international law does not affect the BRICS documents directly and it does not go against the principles of BRICS cooperation announced by Russia. However, there are certain indirect implications. It is clear that the reform deepens divergences between the BRICS countries. The differences in the approaches to the human rights, certain ideological differences will become more acute within BRICS and there is a space for political use of these differences.